Original articleMinimal changes of TNF-α and MCP-1 expression in blood serum of rats subjected to experimental cardiac arrest - Wender, Mieczysław; Michałowska-Wender, Grażyna; Szczech, Józef (Folia Neuropathologica, 2005)
The elucidation of various aspects of the pathomechanism of experimental cardiac arrest may contribute valuable information for the treatment of cardiac arrests in humans. The model of clinical death in rats introduced by Korpatchev et al. was used. An analysis of expression in the blood serum of TNF-α and of MCP-1 was performed as a contribution to this problem. The studied groups included rats 24, 48 hours and 14 days after experimental cardiac arrest. Results: The level of serum TNF-α in all studied animal groups remained unchanged after global cerebral ischemia. MCP-1 expression was decreased only in the group of rats – two weeks after the cardiac arrest. Conclusion: The obtained results indicate that proinflammatory cytokines do not play a key role in the development of delayed neurodegeneration after cardiac arrest. Thus it is not so much the immunological reaction, but a neuroexcitatory mechanism that plays a decisive role in the delayed neuronal death.